SOSIALISASI PROMOSI DIGITAL SECARA ONLINE PADA PELAKU UMKM KARANG TARUNA DI KELURAHAN TELUK LERONG ULU SAMARINDA - Dian Irma Aprianti; Namira Firdha (Journal of Empowerment and Community Service (JECSR), 2022)
The use of online media is one method for promoting and distributing a product or information. At this time, online media tends to focus on product transaction and marketing in order to learn more about the product being sold. It can take a long time and take a long time to gather and distribute data through online media. Because of the growing popularity of the Internet, digital media is becoming more prevalent. However, there are numerous products, including UMKM in Kota Samarinda, that do not use digital data. When it comes to digital media, the Internet serves as a platform for sharing information about the products and services offered by UMKM. UMKM provides a variety of services, including a website for personnel; Additionally, she makes use of her personal social media presence. When it comes to digital marketing, social media is the most important platform for UMKM. As a result, the marketing of UMKM products in Kota Samarinda has a significant impact on the local population. The Usaha Kecil dan Menengah (UMKM) implemented this project in the Ardiansyah area of Karang Taruna, Desa Teluk Lerong Ulu, Kecamatan Sungai Kunjang, Samarinda. This strategy's goal is to improve productivity and quality of life. This was done by using social media to display products and evaluate them through web and broadcast communication in order to achieve digital marketing goals. The study demonstrates that the ability of the UKM Karang Taruna to influence both UMKM and the population is a possibility.